Canny Junk System based on IOT - D. Wilfred Shiju (Indonesian Journal of Electrical Engineering and Computer Science, 2017)
Waste organization is one of the fundamental issue that the world goes up against free of the case of made or making country. The key issue in the waste organization is that the junk canister at open spots stretches out beyond time some time as of late the start of the accompanying cleaning process. It is this way prompts distinctive dangers, for instance, horrendous aroma and disagreeableness to that place which may be the principle driver for spread of various afflictions. To avoid all such hazardous circumstance and keep up open cleanliness also, prosperity this work is mounted on a splendid decline structure. The guideline subject of the work is to develop a sagacious astute deny prepared structure for a real junk organization .This paper proposes a smart prepared structure for junk space by giving an alert banner to the common web server for minute cleaning of dustbin with honest to goodness check based on level of waste filling. This technique is bolstered by the ultrasonic sensor which is interfaced with Arduino UNO to check the level of waste filled in the dustbin and sends the alert to the common web server once if waste is filled.